Analisis Dampak Merger Terhadap Kinerja Karyawan PT. Bank Syariah Indonesia KC Rantau Prapat - Azrin Bahri Harahap; Mustafa Kamal Rokan; Nuri Aslami (Trending: Jurnal Manajemen dan Ekonomi, 2024)
In financial institutions, especially sharia banking, when a merger is carried out it certainly has an impact on the institution itself and its employees, as well as the BSI KC Rantau Prapat bank. This research aims to determine the impact of the merger as well as obstacles and strategies on the performance of the bank's employees. The research was conducted using qualitative methods with a descriptive analysis approach, collected through interviews with several informants, namely bank employees. The research results were measured by three indicators, namely work environment, comfort and employee salary. Measured from the work environment, the merger has a positive impact on employee performance, whereas if measured from employee comfort and salary, the merger has no impact on employee performance.